DNA content and cytogenetic characteristics of Gymnocalycium quehlianum (Cactaceae) along an altitudinal gradient - Martino, Pamela Ayelén (2022)
Important changes in vegetation types occur along elevational gradients. The genusGymnocalycium is endemic to southern South America, and its species are distributed alongelevational gradients. In particular, Gymnocalycium quehlianum is a globular cactus endemicto the Sierras de Córdoba. Studying cytogenetic aspects and DNA content in populationsthroughout their distribution is key to understanding the species. DNA content andcytogenetic characteristics were analyzed in four populations of G. quehlianum (615, 744,948 and 1257 masl). The genome size in the four populations varied between 3.55 and 4.30pg. The populations were diploid (2n = 22). All populations showed the karyotype formula of10 metacentrics (m) + 1 submetacentric (sm). The species presented symmetrical karyotypesand constitutive heterochromatin CMA+/DAPI- associated with nucleolar organizingregions, always found in the first pair of m chromosomes. The 18-5.8-26S rDNA locus isfound in the terminal regions of the first pair of chromosomes m, and the 5S locus is adjacentto the 18-5.8-26S locus. A tendency for DNA content to decrease with increasing altitudewas observed